Peningkatan Kemampuan Guru SMK Kridawisata di Masa Pandemi Covid-19 Melalui Pengelolaan Sistem Pembelajaran Daring - Ahdan, Syaiful; Sucipto, Adi; Priandika, Adhie Thyo; Setyani, Tria; Safira, Wilga; Sari, Kevinda (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Today's online learning technology has created a new paradigm in the process of implementing learning. Face-to-face activities between teachers and students are no longer a necessity to gain knowledge in school. SMK Kridawisata has adequate facilities and infrastructure to support the learning process such as classrooms and laboratories, but there is no system that is able to apply the learning process in networks that can overcome the problems of the standardized learning process during the Covid-19 pandemic. The solution for implementing online learning systems is expected to increase productivity, especially in the learning process, and to optimize the knowledge and ability of teachers in utilizing online-based learning systems in order to overcome problems that occur when teachers are unable to attend. Online learning systems are built using a learning management system (LMS) platform with the availability of features needed in the learning process online.